PENGARUH ASET PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azizah, Eva; Dumadi, Dumadi; Wulandari, Hilda kumala (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the influence of deferred tax assets and deferred tax burden on profitability in companies in the food and beverage sector during the 2021-2023 period. The regression analysis method is used to evaluate the relationship between these variables and the profitability of the company as measured using Return on Assets (ROA). The results of the study show that deferred tax assets have a positive and significant influence on profitability with a significance value of 0.040 indicating a meaningful relationship between deferred tax assets and company profitability. On the other hand, the deferred tax burden did not have a significant effect on profitability with a significance value of 0.255 which exceeded the limit of 0.05, indicating that the deferred tax expense did not have a significant impact on profitability. The F test shows that simultaneously, both variables (deferred tax assets and deferred tax expenses) affect profitability with a significance value of 0.017. The reliability test value showed 44.6%, with the remaining 55.4%, indicating that there was a variation in the data that needed attention. The limitation of this study is that profitability measurement only uses ROA, which may not cover all aspects of a company's profitability. This study provides insight into how the management of deferred taxes affects the financial performance of companies in the food and beverage sector